2018
DOI: 10.5018/economics-ejournal.ja.2018-30
|View full text |Cite
|
Sign up to set email alerts
|

Profit efficiency of banks in Colombia with undesirable output: a directional distance function approach

Abstract: This article analyzes the sources of bank efficiency in Colombia over the period 2000-2011. To perform this research, the authors propose a score of bank efficiency using the directional distance function, which was estimated using data envelopment analysis. Additionally, they use an ordered probit panel regression to explore the effects of some market-related and bank-specific factors on efficiency. The results show that the noninclusion of non-performing loans (NPLs) leads to higher bank inefficiency indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
2
3
0
Order By: Relevance
“…Our results are in line with previous findings that found countries with a high level of CO 2 emissions are less eco-energy efficient than those who have low environmental impact production behavior (Tachega et al, 2021;Bampatsou et al, 2013;Wang et al, 2013). Other findings outside the energy area also confirmed that efficiency models that ignore undesirable outputs tend to overestimate the inefficiency scores (Almanza et al, 2018;Liu et al, 2020). Therefore, in that follows, we interpret only the results obtained from model 2.…”
Section: Energy and Eco-energy Efficiency Scoressupporting
confidence: 92%
“…Our results are in line with previous findings that found countries with a high level of CO 2 emissions are less eco-energy efficient than those who have low environmental impact production behavior (Tachega et al, 2021;Bampatsou et al, 2013;Wang et al, 2013). Other findings outside the energy area also confirmed that efficiency models that ignore undesirable outputs tend to overestimate the inefficiency scores (Almanza et al, 2018;Liu et al, 2020). Therefore, in that follows, we interpret only the results obtained from model 2.…”
Section: Energy and Eco-energy Efficiency Scoressupporting
confidence: 92%
“…The same for private banks was found to be underestimated by 0.2 percent and 0.7 percent. Our findings are similar to those of a previous study concluding that nonconsideration of NPAs could overestimate the inefficiency measurements and underestimate the efficiency of the decision-making unit 48 . Further, the impact is more on public sector banks which clearly endorses the view that the problem of NPAs is worse for public sector banks due to mounting NPAs in their case.…”
Section: Findings and Analysissupporting
confidence: 91%
“…Findings suggest modest risk preference as most suitable for the progress of Chinese banking. Almanza and Rodríguez (2018) proved the importance of including undesirable output into the production model by confirming the significant difference between models when NPL is not considered. Partovi and Matousek (2019) analysed the performance of Turkish banks for the period of 2002 to 2017 by focusing on NPLs as undesirable output.…”
Section: Literature Reviewmentioning
confidence: 82%